Economic assessment of water management in agriculture: managing salinity and waterlogging in the Arkansas River basin and environmental water shortages in the Platte River basin - Houk, Eric E., author; Frasier, Marshall, advisor; Hoag, Dana, committee member; Schuck, Eric, committee member; Gates, Timothy, committee member (Colorado State University. Libraries, 2003)
As irrigated agriculture becomes increasingly threatened by both water scarcity and degradation of land and water, the importance of appropriate water management becomes apparent. This dissertation consists of one essay examining the effects of water transfers from agriculture for improving threatened species habitat in the Platte River Basin and two essays addressing irrigation induced waterlogging and salinization in the Arkansas River Basin. Each essay integrates hydrologic modeling into the economic analysis to evaluate the effects of water management alternatives on agricultural production. In the first essay, Discrete Sequential Stochastic Programming (DSSP) is coupled with a basin-wide hydrologic model to estimate the forgone agricultural value associated with water transfers for endangered species habitat restoration. The value of irrigation water in agriculture was estimated for five agriculturally distinct regions of the Platte River Basin. Irrigation water in the upper-most region of the basin was estimated to be of lowest value in agricultural production. Results indicate that although water transfers from agriculture that originate farther upstream result in less water yield at the habitat, they can be more cost effective. In the second essay, information about current agricultural practices, soil salinity levels, water table depths, and the response functions of crop yields to both waterlogging and soil salinity are used to estimate the current losses associated with waterlogging and salinization. The average forgone profit across the study area was estimated to be $4.3 million annually, or approximately $68/acre per year. This represents the potential of increasing profits by approximately 39% if the effects of waterlogging and soil salinity were removed. The third essay evaluates several types of alternatives aimed at reducing the impact of waterlogging and soil salinization. The general approach taken is to estimate the costs of inputs required and the commensurate effects on agricultural productivity associated with the changes to soil salinity and water table depth. Each method evaluated was capable of increasing agricultural productivity; however, the associated costs were higher. Although the costs were higher than the direct benefits to agricultural production, significant reductions in salt load to the river were estimated to occur at relatively low costs to society.
Keywords: water resources; rivers; studies; agricultural production; water supply; water shortages; endangered and extinct species